Long-term changes in populations of birds near Ukrainian Antarctic station “Akademik Vernadsky” - M. V. Chesalin (Ukrainian Antarctic Journal, 2008)
Quantitative distribution of penguins and other mass species of birds and also features of their behavior and reproduction were studied. Obtained data were compared with results of the previous researches that have allowed to observe tendencies of long-term variability of number in colonies of penguins and in populations of other birds. It was found that in comparison with 70s of the last century on islands Petermann, Pléneau and Booth the quantity of nests of the subantarctic gentoo penguin has increased in 3-4 times, and since 1997 to 2005 it has increased approximately in 2 times. Besides, the natural habitat of this species extends southward and the new most southern colony of gentoo was found on small islands near Moot Point, whereas the large penguins that perhaps belong to the northern subspecies of the gentoo were marked on Pléneau Island. Number of nests of the Antarctic penguin Adeli on islands Petermann, Booth and Yalour has decreased approximately in 2 times from 1993 to 2005. Last years the reduction of numbers of the blue-eyed shag and some other species of birds in the region of the Ukrainian station was marked. The reasons of the changes occuring in colonies of penguins are discussed.